Our Master's Voice Advertising - Rorty, James, 1890-; Pooley, Jefferson, 1976-; Project Muse. (mediastudies.press, 2020)
""I was an ad-man once," James Rorty writes in this classic dissection of the advertising industry. Steeped in Rorty's leftist politics, Our Master's Voice presents advertising as the linchpin of a capitalist economy that it also helps justify. The book set off tremors when it was published in 1934, perhaps because its author so decisively repudiated his former profession. But Rorty and his spirited takedown of publicity were all but forgotten a decade later. The book is a neglected masterpiece, republished in this mediastudies.press edition with a new introduction by Jefferson Pooley"--
Description based on print version record.
Keywords: Electronic books